The case for hybrid ventilated primary schools in Ho Chi Minh City in Vietnam - Vi Le, Thi Ho; Gillott, Mark C.; Rodrigues, Lucélia Taranto (2016)
This study investigates indoor environmental quality and users’ perception in 14 classrooms of a mixed-mode ventilated primary school in Ho Chi Minh City, Vietnam, during the rainy season by qualitative and quantitative research methods. Spot and long-term measurements were recorded, covering a range of environmental parameters such as air temperature, relative humidity, CO2 concentration level, illuminance and sound level. A questionnaire was conducted and answered by 451 children (eight to eleven year olds) to investigate their perception of the thermal and visual comfort, indoor air quality, noise and overall comfort in the classrooms. In addition, 14 teachers were asked to inform the study about their experiences and behaviours in the classrooms. The results were analysed by cross relating the measured environmental conditions and the comfort vote on a seven-point scale.